What happened to the women?: gender and reparations for human rights violations (2006)
What happens to women whose lives are transformed and curtailed by human rights violations? What happens to the voices of victimized women once they have their day in court or in front of a truth commission? Women face a double marginalization under authoritarian regimes and during and after violent conflicts. Nonetheless, reparations programs are rarely designed to address the needs of women victims. What Happened to the Women? Gender and Reparations for Human Rights Violations, edited by Ruth Rubio-Marín, argues for the necessity of introducing a gender dimension into reparations programs in order to improve their response to female victims and their families. A joint project of the International Center for Transitional Justice and Canada’s International Development Research Centre, What Happened to the Women? Includes six country studies of gender and reparations policies: Guatemala, Peru, Rwanda, Sierra Leone, South Africa, and Timor-Leste. The contributors represent a wide spectrum of fields related to transitional justice, and include international human rights lawyers, members of truth and reconciliation commissions, and NGO representatives. What Happened to the Women? Is of immense assistance to gender practitioners and scholars working in the fields of human rights, transitional justice, and peace building. Through their analysis and interpretation of the voices of women, the authors of these case studies begin to make concrete suggestions on how gender advocates can play a more positive role in ensuring that reparation becomes a reality for women affected by conflict. The book is an absolutely essential tool for gender advocates and transitional justice practitioners.